LEGAL CONSEQUENCES OF DETERMINATION IN ARBITRATION THAT ALLEGEDLY CRIME WAS COMMITED - Varapnickas, Tadas (Teisė, 2017)
This article analyses the rights and obligations of the arbitral tribunal, arbitral institution and national court when it is suspected that a crime was committed and arbitration is used in order to hide the crime or legalise the consequences thereof. The article assesses whether the abovementioned institutions have competence to take any measures to prevent the legalisation of a crime. It also examines whether an obligation to inform law enforcement agencies exists.